Shear-induced transformations in the lamellar phase of hexaethylene glycol monohexadecyl ether - Penfold, J; Staples, E; Lodhi, A; Tucker, I; Tiddy, G (1997)
The shear-induced ordering of the lamellar phase of hexaethylene glycol monohexadecyl ether, C 16E 6, in a Couette shear cell has been observed by small angle neutron scattering, SANS. Two distinct lamellae orientations have been identified. At low shear gradients the lamellae are ordered parallel to the flow-vorticity plane, whereas at higher shear gradients the lamellae order parallel to the flow-shear gradient plane corresponding to a rotation through 90° of the axis of orientation. At shear gradients intermediate to those two extremes both orientations are observed simultaneously, this being the first report of such a morphology. A novel extension of shear alignment reported here is the application of oscillatory Couette flow. Here, orientation parallel to the flow-vorticity plane and the intermediate state corresponding to components oriented in the two orthogonal directions are observed. These observations are discussed in the context of recent results of shear-induced effects observed in related systems. The additional information obtained from shear flow alignment and from measurements where the neutron beam is incident in a direction orthogonal to the shear gradient (cell side) and parallel to the flow direction has enabled a re-evaluation of the nature of the "defective" lamellar phase.